What is the role of pre-operative sperm DNA fragmentation index in microsurgical varicocelectomy success? - Wang, Lihong; Jiang, Hui; Jiang, Tao (Frontiers in Surgery, 2026)
ObjectiveThis prospective study aimed to examine the effect of pre-operative sperm DFI on varicocelectomy success.Material and methodsA total of 51 infertile men with unilateral clinical VC who met the inclusion criteria and underwent microsurgical varicocelectomy were enrolled. As described in previous studies, in our study, more than 50% increase in total motile sperm count (TMSC) in post-operative semen analysis was defined as a significant improvement. However, at least a 100% increase was required for patients with a TMSC <5 million in the definition of recovery. The patients were separated as two groups as benefiting from the treatment and not.ResultsAmong the 31 patients who completed the 3-month follow-up, significant improvements were observed in sperm concentration, total sperm count, TMSC, abnormal sperm morphology, and DFI (P < 0.05). Post-operative sperm concentration, total sperm count, and TMSC increased, whereas abnormal sperm morphology and DFI decreased. Although mean DFI decreased across all VC grades, only grade III patients showed a statistically significant reduction (P < 0.05). Of the 31 patients, 16 exhibited semen quality improvement, while 15 did not. Preoperative sperm concentration, total sperm count, TMSC, and DFI significantly differed between the two groups (P < 0.05). A preoperative DFI threshold of ≥28.71% predicted post-operative semen improvement with 92.9% sensitivity and 50.0% specificity.ConclusionsOur study showed that high sperm DFI (≥28.71%) may be a useful pre-operative predictive tool in identifying men who benefit most from varicocelectomy in infertile patients with VC.